Developing project-based worksheet enriched with Pancasila student profile for junior high school - Budi Santoso; K. Kustiyowati; W. Waris (Universitas Muhammadiyah Malang, 2024)
This research was motivated by the learning process carried out by teachers has not facilitated students adequately through the use of LKPD. Teachers tend to use textbooks which contain material summaries and practice questions. The objectives of this research are (1) To describe the validity of P5-based LKPD; and (2) Describe the practicality of P5-based LKPD. The research method used is research and development (R & D) with the ADDIE model, namely analysis, design, development, implementation, and evaluations. The instruments used are validation sheets and teacher and student response questionnaire sheets. From a series of development processes carried out, it can be concluded that the LKPD based on the P5 Bhineka Tunggal Ika theme received a score of 91.75% and is within the very feasible criteria. Meanwhile, for the practicality of the LKPD based on the P5 theme of Bhinneka Tunggal Ika, the teacher gave a score of 90% and was within the very practical criteria and students gave a score of 92.2% and was within the very practical criteria. As a form of follow-up and as a limitation to the research objectives, the researcher recommends testing the effectiveness of LKPD based on the P5 theme of Bhineka Tunggal Ika